Antibody/receptor protein immunocomplex in human and mouse cortical nerve endings amplifies complement-induced glutamate release. (23rd July 2015) - Merega, Elisa; Prisco, Silvia Di; Severi, Paolo; Kalfas, Fotios; Pittaluga, Anna
Highlights: The classic pathway of activation is not involved in the complement-evoked glutamate release. Complement glutamate release is significantly increased in synaptosomes incubated with anti-NH2- CCR5 antibody. C1q deprived serum-induced glutamate release is unaltered in terminals incubated with anti-NH2- CCR5 antibody. Complement glutamate release is unmodified in anti-COOH-CCR5 entrapped synaptosomes. Antibodies recognizing the outer sequence of receptors triggers the activation of complement trough the classic pathway. Abstract: Previous studies have demonstrated that complement alone releases glutamate from human and mouse cortical terminals in an antibody-independent manner. In order to expand our knowledge on complement-mediated effects, we investigated whether the presence of an antigen-antibody complex in synaptosomal plasmamembranes could also trigger complement-induced functional responses that might affect neurotransmitter release. To this aim, we focused on the chemokine 5 receptor (CCR5) expressed in human and mouse cortical glutamate terminals, whose activation by CCL5 elicits [ 3 H]D -aspartate ([ 3 H]D -ASP) release. Preincubating synaptosomes with an antibody recognizing the NH2 terminus of the CCR5 protein (anti-NH2 -CCR5 antibody) abolished the CCL5-induced [ 3 H]D -ASP release. Similarly, enriching synaptosomes with an antibody recognizing the COOH terminus of CCR5 (anti-COOH-CCR5 antibody) prevented the CCL5-induced [ 3 H]D -ASP release. The antagonist-like activity of the anti-NH2 -CCR5 antibody turned to facilitation when anti-NH2 -CCR5-treated synaptosomes were exposed to complement. In these terminals, the releasing effect was significantly higher than that elicited by complement in untreated synaptosomes. On the contrary, the complement-induced [ 3 H]D -ASP release from anti-COOH-CCR5 antibody-entrapped synaptosomes did not differ from that from untreated synaptosomes. Preincubating synaptosomes with anti-beta tubulin III antibody, used as negative control, neither prevented the CCL5-induced releasing effect nor it amplified the complement-induced [ 3 H]D -ASP release. Finally, serum lacking the C1q protein, i.e. the protein essential to promote the antibody-mediated activation of complement, elicited a comparable [ 3 H]D -ASP release from both untreated and anti-NH2-CCR5 antibody-treated synaptosomes. Thus, we propose that antibodies raised against the outer sequence of a receptor protein can trigger the activation of the complement through the classic, C1q-mediated antibody-dependent pathway, which results in an abnormal release of glutamate that could be deleterious to central nervous system.